2021
DOI: 10.3390/app112311492
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Thermal Comfort of COVID-19 Nucleic Acid Sampling Staff in Hot and Humid Environment: A Pilot Study of University Students

Abstract: The current situation of Coronavirus Disease 2019 (COVID-19) prevention and control coupled with the need to work in high-temperature harsh environments makes it necessary to ensure the health and efficiency of medical staff. An experimental outdoor work tent was set up and university students were used to study the thermal comfort of personnel wearing protective clothing in hot and humid environments. The experiment was carried out simultaneously through subjective and objective field tests and physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…In this study, the heat stress response of PPE-clad subjects was evaluated in three different environments (WBGTs = 15, 28, 32 • C) and at two thermal resistance levels of undergarments (I cl = 0.37, 0.75 clo). The physiological parameters and perceptual responses are thus greatly affected by the environment, which is consistent with previous research results [21,31]. Local skin temperature is more significantly affected by environmental changes.…”
Section: Discussion and Limitationssupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the heat stress response of PPE-clad subjects was evaluated in three different environments (WBGTs = 15, 28, 32 • C) and at two thermal resistance levels of undergarments (I cl = 0.37, 0.75 clo). The physiological parameters and perceptual responses are thus greatly affected by the environment, which is consistent with previous research results [21,31]. Local skin temperature is more significantly affected by environmental changes.…”
Section: Discussion and Limitationssupporting
confidence: 91%
“…The comfort temperature zones of participants before wearing PPE were found to be 17.4-21.5 • C; meanwhile, participants wearing PPE required a cooler working environment to maintain thermal comfort. In a previous study [21], field experiments were used to analyze and evaluate the thermal comfort of participants wearing medical protective clothing for nucleic acid detection. The findings emphasized the need for measures to mitigate heat stress in nucleic acid sampling personnel working in high-temperature environments.…”
Section: Introductionmentioning
confidence: 99%
“…The average time of PPE usage was 6.5 h per day. Very similar issues were identified in a field study [3] focused on the heat stress and strain of COVID-19 nucleic acid sampling staff in a hot and humid environment. The results showed that the conditions of the ambient environment identified by the WBGT index between 27 and 29 • C led to a very high heat strain expressed by the mean skin temperature reaching up to 37 • C.…”
Section: Introductionmentioning
confidence: 66%